Meningkatkan Kemampuan Komunikasi Matematis dan Self Confidence Siswa Melalui Model Pembelajaran Problem Based Learning - Risa Nursamsih Lubis; Wardani Rahayu (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2023)
Abstract One of the abilities that is very important to pay attention to in learning mathematics is mathematical communication skills besides that there are other aspects that must be considered, namely students' self-confidence. This study aims to provide an overview as a study of the Problem Based Learning (PBL) model in improving students' Mathematical Communication Ability and Self-confidence. The method used is descriptive, by describing the results of a literature review of at least 30 relevant articles. The results of this study are that there is a positive relationship between students' self-confidence with mathematical communication abilities and the Problem Based Learning Approach is effective in efforts to improve students' mathematical communication skills and self-confidence. Keywords: mathematical communication ability, self confidence, Problem Based Learning learning model